Transformation Of Librarian As Knowledge Manager In Big Data Era - Sutarsyah Sutarsyah; Hendro Subagyo; Noorika R. Widuri; Ariani Indrawati (Prosiding International conference on Information Technology and Business (ICITB), 2019)
Processing big data is complicated caused by its complexity like the quantity of data, the various data format in various representations, and very fast data changes. Librarians are challenged to be able to exploit the potential of big data, they are challenged to analyze and extract knowledge from the data to easily understood and used by users because knowledge is the most important asset and greatest competitive advantage of many organizations. So, the librarian should to improve their skills and be creative to keep up with the new environment. One of the things that can be done by librarians is to strengthen its function as a knowledge manager. This study aims to know how the role of librarians as knowledge managers in the era of big data and what skills needed to be a knowledge manager in the big data era. The study was conducted by a literature review from various sources. The analysis was done descriptively qualitatively based on the sources of literature obtained. The results of the study show the skills that must be possessed as follows: IT skills, literacy, technical and analytical skills, extract, filter and disseminate vital external knowledge, communication skills, advocacy, create, record and store information effectively -strategic planning ability and use information tools effectively.Keywords: Big data, librarian, knowledge management, digital ecology.